THE EFFECT OF MODEL SCIENTIFIC INQUIRY TOWARD SCIENCE PROCESS SKILLS VIEWED FROM SCIENTIFIC ARGUMENTATION - Meutia Kemala Putri (Universitas Negeri Medan, 2017)
The purpose of this research is to determine: the result of students’ science process skill with using scientific inquiry learning model better than conventional learning, science process skill of students who have high average scientific argumentation better than students who have low average scientific argumentation, the interaction between scientific inquiry learning model and scientific argumentation of physics students' science process skill. This research is a quasi-experimental research. The sampling choosed by cluster random sampling. This research instrument used tests of scientific argumentation and science process skills test. The results of this research concluded that: the science process skill of students using scientific inquiry learning model better than conventional learning, science process skill of students who have high average scientific argumentation better than students who have the low average scientific argumentation, and there was interaction between the scientific inquiry learning model and conventional learning with scientific argumentation to improve physics students' science process skill.